(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2023)
Abstract The study aimed to prepare a practical guide for procedures for auditing the strategies of municipal institutions in achieving sustainable development by adopting the idea of ​​the audit matrix through which a classified report is prepared according to the dimensions of sustainable development, by preparing a specialized audit program for the purpose of auditing strategies for achieving sustainable development and emptying the results of the application of each of the paragraphs The program in the audit matrix that was prepared for the purpose of determining the impact of each observation and linking it with the dimensions of sustainable development according to the potential impact of the observation, and the study reached the goal set for it to prepare the proposed guide.